Study of aetiological factors and clinical profiles of neonatal jaundice in the special newborn care unit of tertiary care hospital of Government Medical College, Rajouri, Jammu and Kashmir union territory: a hospital-based study - Iqbal, Javaid; Sharma, Sudekshan; Naaz, Balqies (International Journal of Research in Medical Sciences, 2023)
Background: Neonatal hyperbilirubinemia may be physiological or pathological. Neonatal hyperbilirubinemia is a common condition requiring inpatient treatment and monitoring and many time requires readmission to hospital. Estimated incidence of jaundice in neonates is 60% to 84% of late term and term infants. Present study was undertaken to study clinical profile of neonates with jaundice at our tertiary care centre. Methods: This prospective observational study was conducted in neonates with jaundice admitted in SNCU ward during study period with serum bilirubin more than 10 ml/dl. Results: During study period 339 neonates were considered for presented study. 192 newborns (56.63%) developed jaundice after 72hrs. of birth. Only 28.90% newborns developed jaundice within 24 hrs. Of birth. 61.65% babies were male as compared to 38.34% female babies. Jaundice was most commonly noted in babies delivered at more than 34 weeks gestational age (60.17%), while only 10.02% babies were delivered between 28-32 weeks gestational age. 2500- 4000 gm birth weight babies were 60.14% while only 39.82% babies had weight less than 2500 gms. Incidence of neonatal jaundice was 60.06%, 30.38%, 08.55% in vaginal, caesarean section and instrumental delivery respectively. Physiological jaundice (30.67%), prematurity (25.30%), Rh incompatibility (10.91%), breast feeding/jaundice (10%), ABo incompatibility (6.19) and idiopathic (5.01%) were most common causes noted in our study. Conclusions: Male gender, 2500-4000 gm birth weight, vaginal delivery, physiological delivery, prematurity were common causes associated neonatal jaundice in our study. Parent counselling and monitoring of baby is most important in management of neonatal jaundice.